Kode Etik Profesi Guru - Indriawati, Prita; Yulianto, Mustofa; M. Simamora, Evalilis (Jurnal Syntax Fusion, 2023)
The code of ethics for the teaching profession is a guide as well as the moral basis for a teacher in professional behavior, including Guidance and Counseling teachers. The Importance of Professional Codes of Ethics Codes of ethics are a way to improve organizational ethics so that individuals can act ethically. Meanwhile, violations of the teaching professional code of ethics are violations of norms, values ​​and written professional rules that explicitly state what is right and good for a profession in a society that is influenced by misconceptions, lack of preparedness of teachers and students, and lack of inculcation of character. By using a literature study, in practice violations of the professional code are still found in the administration of education. To overcome violations of the teaching professional code of ethics, one of them is by taking firm action and imposing severe sanctions on individual teachers who commit cases of professional ethics because it is very detrimental to the teacher as a profession whose one of its duties is to set a good example towards students